Revitalisasi Peran Perangkat Kewilayahan Melalui Pelimpahan Sebagian Kewenangan Bupati Fakfak Kepada Kepala Distrik Fakfak - Abdul Anwar Sanaki; Djohermansyah Djohan; Sampara Lukman (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2023)
The authority given to several fields overlaps, for example authority has been given in accordance with Regent Regulation Number 33 of 2012 concerning the Delegation of Part of the Regent's Authority to District Heads in the Fakfak Regency Government Environment, but in practice this is not the case, the agencies at the Regency level are in charge of the field/sector In fact, they almost never coordinate with the District, so that the functions of the District according to Regent Regulation Number 33 of 2012 are not carried out properly. This research uses a qualitative method with a descriptive approach using theory from Iglesias (Kaho, 1997: 59) with primary and secondary data sources. Data collection techniques were carried out using interviews, observation and documentation, data analysis techniques used were data reduction and drawing conclusions. Based on the research results, it was concluded that the ideal revitalization of the role of regional apparatus through delegating the authority of the Regent of Fakfak to the Head of the Fakfak District must be followed by increasing financial capacity, apparatus capability, community participation and non-human resource capabilities. The implementation of the role of regional apparatus through the delegation of part of the authority of the Regent of Fakfak to the Head of the Fakfak District has not been optimal, where the delegation of authority for the fields of government, economic development, education and health and civil service has not been fully followed by giving full authority to the Head of the District, or it seems still half-hearted because The district head's space for movement is always monitored by the regent regarding the implementation of his authority. The process of delegating authority is still not able to run optimally because the district's resources are still limited so that service activities are not yet optimally felt by the community.